Effect of intraoperative fluid volume on postoperative pulmonary complications in thoracic surgeries: A systematic review and meta-analysis - Shreya Das Adhikari; Nitin Gupta; Mukund Gupta; Savan K. Nagesh; Souvik Chaudhuri; Rakesh Garg (Indian Journal of Anaesthesia)
Background and Aims: There is a lack of clear recommendations on fluid strategies in patients undergoing thoracic surgeries. The primary objective of this study was to compare the amount of intraoperative intravenous fluid (IVF) infused between those who developed postoperative pulmonary complications (PPCs) and those who did not. Methods: All studies comparing PPCs in intraoperative restrictive versus liberal fluid therapies were included. Those studies where the average fluid infused was compared between PPC and the ‘no PPC’ groups were also included. The pooled mean difference in IVF between patients with and without PPC and the pooled risk ratio of PPC in restricted versus liberal fluid arms were calculated. Results: Articles from PubMed (n = 157), EMBASE (n = 724) and citation searching (n = 4) were included. After excluding duplicates, title–abstract screening for 759 articles and full-text screening for 24 articles were done. The mean fluid infused in the 11 included articles was significantly higher in those with PPC (mean difference: 1.51 ml/kg/h, P = 0.001). The pooled proportion of PPC in liberal fluid arms was higher than in restricted fluid arms [risk ratio = 0.58 (95% confidence interval: 0.33, 1.02), P = 0.06]. There was high heterogeneity in both the meta-analyses. Conclusion: The meta-analysis showed that increased intraoperative IVF is associated with higher PPCs, and a restricted fluid strategy might be safer to reduce PPCs. However, since most studies were observational with a high risk of bias and high heterogeneity, well-conducted randomised controlled trials are needed to derive recommendations.